2016
DOI: 10.1038/srep27424
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability in the occurrence of wintertime haze in central eastern China tied to the Pacific Decadal Oscillation

Abstract: Haze is a serious issue in China with increasing concerns, and understanding the factors driving decadal-scale variations in haze occurrence is relevant for government policymaking. Using a comprehensive observational haze dataset, we demonstrate notable decadal fluctuations in the number of haze days (HD) during winter in central eastern China, showing a decline since the mid-1980s. The leading mode of the wintertime HD features an increasing trend for 1959–2012 in eastern China, highly correlated with China’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 50 publications
4
82
0
Order By: Relevance
“…As shown in Figure 5, there is a significant decreasing trend in the DECI during the period from 1979 to 2013, which is highly consistent with the previous findings observed for the winter haze events (e.g., . Furthermore, it is noted that the haze variability in China can be mathematically broken into three components based on the case we are analysing here: a long-term trend, inter-decadal variation, and inter-annual variations (Cohen, 2014; Zhao et al, 2016). Zhao et al (2016) showed that long-term trend of the winter haze reduction over eastern China is closely related to the China's economic development and the inter-decadal timescale variation has a close relationship with the SST anomalies related to the PDO.…”
Section: Inter-annual Variation Of Spring Dec Over the Ncpmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5, there is a significant decreasing trend in the DECI during the period from 1979 to 2013, which is highly consistent with the previous findings observed for the winter haze events (e.g., . Furthermore, it is noted that the haze variability in China can be mathematically broken into three components based on the case we are analysing here: a long-term trend, inter-decadal variation, and inter-annual variations (Cohen, 2014; Zhao et al, 2016). Zhao et al (2016) showed that long-term trend of the winter haze reduction over eastern China is closely related to the China's economic development and the inter-decadal timescale variation has a close relationship with the SST anomalies related to the PDO.…”
Section: Inter-annual Variation Of Spring Dec Over the Ncpmentioning
confidence: 99%
“…Furthermore, it is noted that the haze variability in China can be mathematically broken into three components based on the case we are analysing here: a long-term trend, inter-decadal variation, and inter-annual variations (Cohen, 2014; Zhao et al, 2016). Zhao et al (2016) showed that long-term trend of the winter haze reduction over eastern China is closely related to the China's economic development and the inter-decadal timescale variation has a close relationship with the SST anomalies related to the PDO. However, in our case, our findings are quite different with respect to the spring DECI on the inter-annual timescale.…”
Section: Inter-annual Variation Of Spring Dec Over the Ncpmentioning
confidence: 99%
“…Previous studies have suggested that there is a close relationship between the occurrence of winter haze pollution in the Beijing-Tianjin-Hebei region and atmospheric circulation at middle to high latitudes over a long-term perspective 35–37 . In addition, on interannual time scales, the air pollution across central and eastern China or even South Asia in the winter and summer is closely related to the East Asian winter and summer monsoons, respectively 3845 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2015) by Arctic sea ice variability, a finding confirmed by Zou et al (2017). Zhao et al (2016) also found that the Pacific Decadal Oscillation can influence the number of winter haze days in central-eastern China, with a statistically significant correlation coefficient of 0.66 between the Pacific Decadal Oscillation index and wintertime haze days. Li, Zhang, et al (2016) reported a statistically significant correlation coefficient of À0.41 between East Asian winter monsoon index and wintertime fog-haze days.…”
Section: Introductionmentioning
confidence: 78%